New Dynamics of Risk and Responsibility: Expanding the Vision for Accident Compensation - Gaskins, Richard (Victoria University of Wellington Law Review, 2004)
A holistic approach towards risk management must recognise the interconnectedness of economic and social structures. In this article, Gaskins focuses on the concept of “network societies”, which look to increase communication and organisation within their sphere of influence. While recognising that networks have the ability to regulate the distribution of risk across economic groups in society, Gaskins highlights the potential for networks to displace risk onto vulnerable sectors, thus essentially increasing risk levels for those outside the network. In the realm of health and safety, this can push the responsibility for occupational accidents onto already burdened families and communities. The development of the ACC system in New Zealand originally embraced a coherent approach to risk management. Gaskins argues that this approach has become displaced, and should be reestablished as the foundation of the ACC system. This article does not attempt to prescribe a way forward for ACC, but rather aims to highlight areas of particular concern, which require consideration in relation to the further development and advancement of ACC in New Zealand.